PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL PENGETAHUAN DAN PEMELIHARAAN ALAT JAHIT - Nurwana; Muhammad Yahya; Abdul Muis Mappalotteng (UNM Journal of Technology and Vocational, 2025)
The purpose of this study is to determine the needs analysis, research design, relevance, practicality, and effectiveness of the digital education module. One type of applied research is research and development (R&D). The development process refers to the ADDIE model. Data will be collected through observation, interview, and questionnaire methods. During the initial phase of development, a needs analysis conducted based on observations and interviews with course instructors revealed that students with limited skills and time constraints were the group most affected by technology. The research design shows that the E-module was developed using Canva and FlippingBook applications. The results of the validity of the module's data showed a score of 95% for media experts and 97% for material experts, which was included in the category of very valid. The results of practical relevance data were obtained from a survey conducted on students, where 81.33% of respondents categorized the module as very practical. The results of the effectiveness data were determined based on the achievement of student learning outcomes, with the pre-test and post-test scores in the effective category with a score of 74.35 points and the average improvement in learning outcomes in the high category with a score of 0.74 points. Based on the results of this study, it can be concluded that this E-module is useful and can be implemented in the course "Knowledge and Maintenance of Sewing Tools" in the Diploma 3 (D3) Fashion Design Program, Faculty of Engineering, State University of Makassar